Relevância da ultra-sonografia dos tendões flexores em cavalos puro sangue de corrida na adaptação ao treinamento - Greig, Carolina Roxana (2002)
The cross-sectional area (CSA) of the superficial digital flexor tendon (SDFT) and deep digital flexor tendon (DDFT) of twenty four thoroughbreds was ultrasonographically evaluated before and during their initial training to determine the effect of exercise on the tendon CSA, texture and echogenicity to characterize the response to training. Ultrasonographic transverse images of the left forelimb were obtained every fifteen days. The SDFT CSA of zones IA and IIIA showed a decrease (p<0.05, f=0.010 e f=0.023 res.) during the breaking and training period and an increase (p< 0.05) of zone IIIC (f=0.039). Evaluating just the training period, SDFT CSA results of zones IA, IIIA and IIIC were similar. The DDFT showed no variation during the breaking phase but when the training phase was evaluated there was a decrease(P<0.05) in zones IA (f=0.006) and IIIA(f=0.006). Evaluating both breaking and training periods the DDFT showed a decrease (P<0.05) in zones IA (f=0.027), IIIA (f=0.0001) and IIIB (f=0.0031). Fiber texture and tendon echogenicity showed no significant difference between breaking and last reading during training. This study failed to provide evidence of ultrasonographic image variations that would indicate adaptation of both SDFT and DDFT to exercise during training of thoroughbred horses.